Sukuk Ijarati Hukumati Indonesia - DONI, ERFAN; , Dr. Muh. Muinudinillah Basri, MA; , Dr. Erwandi Tarmizi, MA (2016)
This work is focused on the practice that applied by government of Indonesia to publish the Surat Berharga Syariah Negara ( SBSN Ijarah) in which the beginning of release in 2008. by considering theory of surat berharga ijarah in Islamic perspective ( sharia Islamic ). The research goal is to examine and get deep understanding the theory of Islamic fiqih in which applied to akad, publication, lifecycle, due rate, repurchase by due date and related to the practice of Surat Berharga Ijarah in Indonesia government. Type of this research is literature review by employing inductive descriptive statistic method. The finding of this research is three types of surat berharga ijarah based on fiqih islam including sukuk milkiyah ushul al mu'jarah, sukuk milkiyah manafi' and sukuk milkiyah khidmad. In the practice, all of the letter types should be refer to Kaidah Fiqih Islam if in the process of publication, marketing, and repurchasing was in due date. There are three types of SBSN ijarah, including sukuk ijarah sale and lease back, sukuk ijarah asset to be leased and sukuk ijarah khidmat. These SBSN was not suitable to syariah islam on jual beli fiktif. Guarantying the funding from investor by purchasing the expired surat berharga ijarah was not eligible to kaidah perwakilan on sukuk ijarah khidmat.